El Crédito Bancario y las Pymes en Ecuador - Espinoza Rosero, Gloria Belén (2020)
The different contributions on SMEs and access to financing represent a topic of great interest due to the importance of this group of companies in the economic growth of the countries. This work aims to obtain a visualization of bank credit and the access of SMEs to it, through a descriptive study of the amounts granted in Private and Public Banking, as well as the different types of credit portfolio segments available, highlighting those destined to credits for SMEs. The results indicate that Private Banking is the predominant one in the Ecuadorian Financial System. On the other hand, regarding credit to SMEs, it is evident that both in Commercial Credit and Productive Credit from Private Banks, the Credit granted to large companies predominates. Public Banking has directed funds to Productive Credit in favor of SMEs, but the same is not the case with Commercial Credit, which granted more resources to large companies. The foregoing allows us to conclude that access to financing for SMEs is limited.